Study on Serum Levels of Thyroid Hormones and Thyroid Stimulating Hormone in Different Trimester of Normal Pregnancy (Ibrahim Cardiac Medical Journal, 2012)
Objective: The present study was conducted to study the changes in serum levels of thyroid hormones and thyroid stimulating hormone (TSH) in different trimesters of normal pregnancy.Methods: This cross-sectional study was conducted in the Department of Physiology, Rangpur Medical College Hospital over a period 1 year from July 2008 to June 2009. Apparently healthy pregnant women aged between 20 - 35 years were consecutively included in the study. Patients suffering from thyroid disorders or any other systemic diseases and lactating mothers were excluded from the study. A total of 100 subjects - 75 pregnant women (25 selected from each trimester of pregnancy) and 25 non-pregnant women were purposively selected as case and control groups respectively.Result: The mean age was almost identically distributed between the two groups (23.8 ± 3.9 vs. 24.9 ±4.6, p = 0.343). Lower class patient was predominant in case and control group (68% vs. 64%, p =0.756). The mean serum T3 level was higher in case group compared to control group. The mean serum T3 level was identically distributed in 1st and 3rd trimester (p = 0.536 and p = 0.145 respectively) but significant difference was found in 2nd trimester (p = 0.001). The mean serum T4 level of control group did not experience any change throughout the whole observation period. The serum T4 level was 210 nmol/L at 1st trimester then it began to increase almost a plateau at 2nd   trimester and then gradually dropped 232.2 nmol/L at third trimester. The mean serum TSH level was 1.1 mIU/L at 1st trimester then it began to increase sharply assumed a mean score 1.3 mIU/L at 2nd trimester. From 2nd trimester onwards it began to decrease upto the end of observation when no change in the non-pregnant women in 1st, 2nd & 3rd trimester.Conclusion: Thyroid hormones (T3, T4) increase in the 2nd trimester of pregnancy and fall again in the 3rdtrimester but TSH does not experience any significant change throughout the pregnancy.Ibrahim Cardiac Med J 2012; 2(2): 19-23